Five-Years Angiographic Follow-Up of Wide-Neck Intracranial Aneurysms Treated With LEO Plus Stent - Pumar, José M.; Sucasas, Paula; Mosqueira, Antonio; Vega, Pedro; Murias, Eduardo (Frontiers in Neurology, 2021)
Background: This study aimed to evaluate the angiographic and clinical outcome, with emphasis on long-term follow-up, of the LEO Plus stent for complex intracranial aneurysms treated in a single center. Methods: We retrospectively examined a prospectively maintained database of patients treated with LEO Plus devices between January 2004 and December 2016. Data regarding patient demographics, aneurysm characteristics, and technical procedures were analyzed. Angiographic and clinical findings were recorded during the procedure and followed up over a period of at least 5 years Results: We identified 101 patients with 116 aneurysms. In 16 patients, the stent could not safely be placed. Thus, a total of 97 LEO Plus devices were implanted in 97 aneurysms of 85 patients. Adverse events (acute and delayed) were observed in 21.6% of cases (17/85), and most were resolved (70.6 %; 12/17). Five years after the procedure, total morbidity and mortality were 2.3% (2/85) and 3.5% (3/85), respectively. Long-term imaging follow-up showed complete occlusions, neck remnants, and residual aneurysms in 73.1% (57/78), 14.1% (11/78), and 12.8% (10/78) of cases, respectively. Conclusions: Long-term results of treatment of brain aneurysms with Leo stent show high rates of adequate and stable occlusion over time, with an acceptable morbidity and mortality